Nuclear Medicine Physics - Sajid Bashir; Aamir Shahzad (IntechOpen, 2019)
This book offers the foundation for the education and research of medical physicists starting their university studies in the field of the physics of nuclear medicine. The book is equally beneficial to those wishing to advance their knowledge in this area. It provides, in the form of a syllabus, a comprehensive overview of basic medical physics knowledge required in modern nuclear medicine. It offers a guide to nuclear medicine, including radionuclides in medicine for diagnosis, staging of disease, therapy, and monitoring the response of a disease process. This book comprehensively covers a broad range of topics, including but not limited to radioactivity and radionuclide generators, operation of non-imaging and imaging instruments, radiation biology, and radiopharmacy.
English
Keywords: Physical Sciences; Engineering and Technology; Radiobiology; Biophysics; Physics